Partnership with the Private Sector as a Local Development Leverage - Rutkowski, Jerzy; Mataśka, Kamila (Partnerstwo publiczno-prywatne jako czynnik rozwoju lokalnego, 2011)
The purpose of the paper is to present the influence of public-private partnership on local development. Aside from the model of public management with the participation of the private sector, the determinants and factors of local development are also presented. The closing part evaluates PPP in local development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 813-821
Keywords: public-private partnership; local development; local self-government; development factors